Pengaruh Penerapan Aspek Keperilakuan Pada Etika Akuntan Terhadap Kinerja Karyawan - Riska Saputri; Risa Hartini; Shavira Rizki Maharani (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Ethics in accounting is a fundamental aspect in the world of accounting, involving moral principles and values that accountants must adhere to in carrying out their responsibilities. Beyond technical aspects such as compliance with accounting standards, ethical considerations also encompass behavioral aspects involving interactions with colleagues, superiors, and clients. The implementation of behavioral aspects in accounting ethics significantly influences employee performance. Accountants who apply moral principles and positive values in their work affect their interactions with others, building good relationships with colleagues, superiors, and clients. This enhances team collaboration, effective communication, and wise conflict resolution. This research purpose to uncover the impact of the implementation of behavior aspects in accounting ethics on employee performance, in line with research issues related to investigate the result of these aspects on employee performance.